GIs and Fräuleins : the German-American encounter in 1950s West Germany - Höhn, Maria, 1955- (University of North Carolina Press, 2002)
With the outbreak of the Korean War, the West German state of Rhineland-Palatinate became home to some of the largest American military installations outside the USA. This book explores the social, cultural and economic changes that resulted from this German-American encounter.